Perancangan Konsep Pengembangan Buku Ajar Geografi Bermuatan Ketimpangan Ruang pada Jenjang SMA - Farkhan, Muhammad Robith; Maryani, Enok (Paedagogie, 2026)
The study of spatial inequality as a unique study of the discipline of geography that can be embedded in geography textbooks. Currently, geography textbooks in high schools are considered to still focus on instilling complex scientific concepts and are still not contextual, and there is little encounter of actual problems and understanding of local geography. This is very different when compared to geography textbooks used by students in various countries, referring to "Geography for Life" which is more adapted to the current and future needs of students. This study was conducted with the aim of determining the development of the concept of geography textbooks that include the problem of spatial inequality at the high school level. The research method used a literature study to form a good textbook concept that is ready to be developed. The results of the study indicate that the development of textbooks can be done by considering various technical matters related to the embedding of theory and practice that are adapted to the applicable curriculum. It is concluded that the development of the concept of textbooks containing the problem of spatial inequality is carried out systematically to meet students' learning needs.